Comprensión lectora en estudiantes de sexto grado de primaria, según género y tipo de institución educativa: Ventanilla - Callao - Rivadeneira Bran de Laureano, Leonor (2010)
Comparative descriptive research on reading comprehension in elementary students, in relation to gender and type of school. The sample consisted of 110 students (55 girls and 55 boys) from the 6th grade of a public school and another parish. We used the Reading Comprehension Test of Linguistic Complexity 6 is A Progressive CLP reliability was studied with the method teas-retest Spearman rho coefficient of .78 and construct validity with confirmatory factor analysis method, it was concluded that the test is reliable. The results show that significant differences exist among students by type of institution with a t value of -3.194 and a significance of 0.00. In gender terms there are no significant differences.